The impact of red meat and processed meat consumption on the risk of development and relapse of ulcerative colitis: a systematic review and dose-response meta-analysis - Zhang, Yangyang; Yu, Yitong; Jiang, Ziyun; Yu, Junhong; Zhang, Zeyang; An, Zhuojia; Du, Yanhong; Mao, Yiqing; Hu, Lanshuo; Tang, Xudong; Zhao, Yingpan; Mao, Tangyou (Frontiers in Nutrition, 2025)
BackgroundConsumption of red and processed meats has been classified as probably carcinogenic and carcinogenic to humans, respectively. However, the association between their consumption and the incidence or recurrence of ulcerative colitis (UC) remains unclear. This study aims to systematically evaluate the dose–response relationship between red or processed meat consumption and UC.MethodsDatabases including PubMed, Cochrane Library, Web of Science, Embase, CNKI, VIP, Wanfang, SinoMed, Yiigle, and ICTRP were searched from inception through July 2024. Pooled relative risks (RRs) with 95% confidence intervals (CIs) were estimated using random-effects or fixed-effects models based on heterogeneity. A dose-response meta-analysis was conducted using R 4.4.2.ResultsEighteen studies comprising 1,384,024 participants were included, all rated as moderate to high quality. Red meat consumption was significantly associated with an increased risk of UC development [RR = 1.21, 95% CI (1.03, 1.42), p = 0.020]. Processed meat consumption showed a tendency toward increased UC risk, although not statistically significant [RR = 1.54, 95% CI (0.99, 2.42), p = 0.058]. Neither red nor processed meat consumption was significantly associated with UC recurrence. Dose–response analysis indicated that each additional 100 g/day of red meat intake increased UC incidence risk by 65% [RR = 1.65, 95% CI (1.30, 2.09)].ConclusionBased on very low-certainty evidence, increased red meat intake may be associated with a potential risk of developing UC. However, there is currently insufficient evidence to support an association between red or processed meat consumption and the recurrence of UC. Future studies with long-term follow-up and rigorous design are warranted to verify these findings and explore underlying mechanisms.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024573557, identifier (CRD42024573557).